Analysis of Pork Fatty Acid in Cornet in The Curug Market Using Gas Chromatography - Widyatari, Ade Dwi; Rusdiana, Nita; Rasydy, Laode Akbar (Universitas Muhammadiyah Yogyakarta, 2024)
Counterfeiting of food products with non-halal ingredients is starting to become a new problem in Indonesian society, the majority of whom are Muslim. One example of processed meat that is susceptible to the addition of pork components is corned beef. This research aims to determine the content and levels of fatty acids in corned beef. The method used to analyze halal food products is the GC method. The results showed that corned beef 1, 2, and 3 had dominant fatty acids such as myristic acid (1.58), (2.08), and (1.54), palmitic acid (49.91), (48.19) and (48.67), stearic acid (9.27), (10.20) and (7.24), oleic acid (58.89), (49.37) and (59.64), and linoleic acid (12.78), (8.16) and (11.53).